2019
DOI: 10.1002/acr2.1016
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Periods, and “The Pill”: Exploring the Reproductive Experiences of Women with Inflammatory Arthritis

Abstract: ObjectiveWomen with inflammatory arthritis appear to have fewer children as compared with healthy women, but few studies have assessed how patients' attitudes and decision making influence their family sizes. Little is also known about how patients experience other aspects of their reproductive lives, such as menstruation and contraception.MethodsWe partnered with ArthritisPower, a patient‐powered research network, and its associated online patient community, CreakyJoints, to create and disseminate a survey am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Our findings mirror published literature reporting a dearth of reproductive health information available to rheumatology patients of child-bearing age [5,6,18], and young adults with other chronic diseases [19]. In other studies, women reported making key decisions about reproductive health based on misinformation, anxiety, and fear versus medical input and reliable resources [6,7]. Similarly, our participants, who had a broad spectrum of diagnoses and medications used, voiced that they had insufficient information to make informed decisions about future pregnancy and family planning, and did not know where or from whom to obtain the most accurate advice.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings mirror published literature reporting a dearth of reproductive health information available to rheumatology patients of child-bearing age [5,6,18], and young adults with other chronic diseases [19]. In other studies, women reported making key decisions about reproductive health based on misinformation, anxiety, and fear versus medical input and reliable resources [6,7]. Similarly, our participants, who had a broad spectrum of diagnoses and medications used, voiced that they had insufficient information to make informed decisions about future pregnancy and family planning, and did not know where or from whom to obtain the most accurate advice.…”
Section: Discussionsupporting
confidence: 88%
“…In spite of the unmet facet of clinical care reported almost two decades ago [ 16 ], AYAs and their parents continue to report dissatisfaction as to how reproductive health is addressed in pediatric rheumatology clinics [ 17 ]. Our findings mirror published literature reporting a dearth of reproductive health information available to rheumatology patients of child-bearing age [ 5 , 6 , 18 ], and young adults with other chronic diseases [ 19 ]. In other studies, women reported making key decisions about reproductive health based on misinformation, anxiety, and fear versus medical input and reliable resources [ 6 , 7 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study focused on responses related to women's decision-making and information-seeking regarding arthritis medication use during pregnancy and lactation. Additional details about our survey have been previously described (18). This study was approved by the Duke University Institutional Review Board (PRO00079454).…”
Section: Survey Contentmentioning
confidence: 99%
“…due to disease-related physical and functional limitations), uncertainty around medication use (e.g. stopping medications, adverse pregnancy and fetal outcomes), and fears about RA hereditability (15)(16)(17)(18)(19)(20)(21). Despite recognition that females with RA are not meeting their reproductive goals, there are no studies examining the process of reproductive decision-making, speci cally the trade-offs related to managing disease activity and potential pregnancy.…”
Section: Introductionmentioning
confidence: 99%